An LPV pole-placement approach to friction compensation as an FTC problem - Patton, Ron J.; Chen, Lejun; Klinkhieo, Supat (Zielona Góra: Uniwersytet Zielonogórski)
The concept of combining robust fault estimation within a controller system to achieve active Fault Tolerant Control (FTC) has been the subject of considerable interest in the recent literature. The current study is motivated by the need to develop model-based FTC schemes for systems that have no unique equilibria and are therefore difficult to linearise. Linear Parameter Varying (LPV) strategies are well suited to model-based control and fault estimation for such systems
Keywords: friction; linear parameter varying; fault detection and diagnosis; linear matrix inequality; pole-placement